Rōngsīkhāo chumchon: nǣokhit læ nǣothāng kānphatthanā sētthakit thō̜ngthin thī yangyư̄n - Sunthō̜nchai Chō̜pyot (Khrōngkān Phalit læ Phœ̄iphrǣ Tamrā læ Ngān Wichākān (COPAG Press), Witthayālai Kānmư̄ang Kānpokkhrō̜ng, Mahāwitthayālai Mahā Sārakhām, 2018)
Community rice mills for economic development in the local community of Thailand.